The Use of Rumpon: Fish Aggregate Device (FAD) Made of Artificial Boat for Fishing Activities in Pasar Sorkam Village, Central Tapanuli Regency, North Sumatera Province - Manurung, Vindy Rilani; Susetya, Ipanna Enggar; Sebayang, Nur Ulina Warnisyah; Harahap, Zulham Apandy; Husaini, Hasbi; Desnamrina, Kenni Cendekia; Dewinta, Astrid Fauzia (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Pasar Sorkam Beach, Binasi Village is an area with many large coastal areas with an area of ​​3.85 km2, with a population of 1262 people and an average livelihood as a fisherman, with a total catch of 40234.7 tons. Based on information from POKMASWAS and temporary fishing groups, there are problems, that is the decline in fish catches due to damage to the ecosystem caused by illegal fishing and fishing that is Harmful to the environment, so that a solution is needed to solve this problem, namely by making fish aggregate device (FAD) called Rumpon that support sustainable fisheries so that it is in line with Sustainability Development Goals (SDGs) number 14. The method of implementing this activity is the educational method with demonstrations and counseling through four stages, preparation of activities, field practice, socialization, monitoring and evaluation. The results and discussions obtained were that preparation of activities was carried out after site surveys and literature studies with experience in using Rumpon, construction planning and determining the release of Rumpon, field practice was carried out by releasing Rumpon by all activity participants and accompanied by the Indonesian Navy, the release is intended as a new fishing ground for fishermen, socialization of activities attended by all participants, monitoring and evaluation, monitoring through the head of POKMASWAS, evaluation using a questionnaire with 15 questions about the condition of fishermen, community service activities are conducive and fishing group mitra are very enthusiastic about this activity.